Regional and socio-demographic predictors of dietary proficiency of adolescent girls in Nigeria - Olumakaiye, Motunrayo Funke; Nzeagwu, Ogechi Chinwe; Otitoola , Olufunmilola Comfort; Ariyo, Oluwaseun; Abe, John; Popoola, Bolanle; Gbemileke, Ayodele; Akinyotu, Oseyemi Esther (The North African Journal of Food and Nutrition Research, 2024)
Background: Dietary behaviors of female adolescents are of increasing concern due to their critical role in determining long-term health outcomes. Aims: This study aimed at investigating dietary proficiency of adolescent girls aged 10 – 19. Methods: A descriptive cross-sectional study was conducted with 2261 in-school female adolescents aged 10 – 19 years. Participants were selected using a multistage stratified random sampling procedure was used to select participants from three geopolitical zones in Nigeria. Two states were selected from three geopolitical zones in Nigeria: North-Central (Kogi and Niger States), South-East (Abia and Imo States), and South-West (Osun and Ondo States). A validated questionnaire was employed to collect data on sociodemographic variables, Dietary Diversity (DD), Nutrition Knowledge (NK), and Dietary Behavior (DB). These variables were combined to define Dietary Proficiency. Data were analyzed using SPSS version 24. Chi-square test assessed regional associations, while logistic regression analysis was used to identify predictors of dietary proficiency (DP). Statistical significance was set at p < 0.05. Results: Significant regional variations were observed in DD (χ2 = 36.069), NK (χ2 = 56.895), DB (χ2 = 176.52), and DP (χ2 = 40.551). Older girls residing in peri-urban location, from Igbo ethnic group, and moderately large household predicted a likelihood of higher DD with odd ratios exceeding 1. Larger household size (OR = 1.056, 95% CI = 0.813 – 1.373) predicted higher NK. Residing in South-East region (OR = 2.030, 95% CI = 1.640 – 2.513) and being in the mid-adolescent girls (14 – 16 years) (OR = 2.093, 95%CI=1.589 – 2.756) doubled the likelihood of high DB. Predictors of higher DP included older age (OR = 1.160, 95% CI = 0.923 –1.457) and residence in the South-East region (OR = 1.148, 95% CI = 0.883–1.49). Conclusion: Regional and sociodemographic differences significantly influenced dietary proficiency among adolescent girls. Addressed these disparities through targeted nutrition education and awareness programs is crucial for promoting healthier dietary behaviors and improving overall dietary proficiency in this population. Keywords: Dietary Factors, School Adolescent Female, Food Choices, Food Intake, Nigeria.